2004
DOI: 10.1200/jco.2004.03.089
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Humanized Anti-Epidermal Growth Factor Receptor Monoclonal Antibody h-R3 in Combination With Radiotherapy in the Treatment of Locally Advanced Head and Neck Cancer Patients

Abstract: h-R3 is a well-tolerated drug that may enhance radiocurability of unresectable head and neck neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
230
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(237 citation statements)
references
References 29 publications
7
230
0
Order By: Relevance
“…Nimotuzumab was previously shown to induce the regression of A431 tumour xenografts in vivo as a result of inhibition of both tumour cell proliferation and tumour angiogenesis (Crombet-Ramos et al, 2002). Immunohistochemical analysis of tumour specimens from head and neck cancer patients treated with the combination of nimotuzumab and radiation also showed evidence of antiproliferative and antiangiogenic effects (Crombet et al, 2004). These observations suggest that effects of nimotuzumab on both NSCLC cell proliferation and tumour angiogenesis might contribute to the enhancement of the antitumor efficacy of radiation by this antibody observed in the present study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nimotuzumab was previously shown to induce the regression of A431 tumour xenografts in vivo as a result of inhibition of both tumour cell proliferation and tumour angiogenesis (Crombet-Ramos et al, 2002). Immunohistochemical analysis of tumour specimens from head and neck cancer patients treated with the combination of nimotuzumab and radiation also showed evidence of antiproliferative and antiangiogenic effects (Crombet et al, 2004). These observations suggest that effects of nimotuzumab on both NSCLC cell proliferation and tumour angiogenesis might contribute to the enhancement of the antitumor efficacy of radiation by this antibody observed in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…In early clinical trials, nimotuzumab has shown a longer half-life and a greater area under the curve (AUC) in comparison with other anti-EGFR antibodies (Crombet et al, 2003). A phase I/II trial showed that nimotuzumab was well tolerated and enhanced the curative potential of radiation in patients with advanced head and neck cancer (Crombet et al, 2004). Given that little is known of the antitumor action of nimotuzumab in NSCLC, we investigated the growth-inhibitory effects of this mAb alone and in combination with radiation in NSCLC cell lines with differing patterns of EGFR expression.…”
mentioning
confidence: 99%
“…Recent studies have exhibited the existence of shed or solubilized forms of HER2/neu (Crombet et al, 2004;Semba et al, 1985). The exact method for the release of soluble truncated HER2/neu and the full-length transmembrane protein is not known (Breuer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The use of targeted agents against molecular markers belonging to the epidermal growth factor receptor (EGFR) family has recently become integrated into the treatment protocols of many malignancies, such as breast cancer (Ciardiello, 2001;Crombet et al, 2004;Soulieres et al, 2004;Cavalot et al, 2007;Radpour et al, 2009). Despite recent improvements in the diagnosis and treatment of cancer, there are still many difficulties in evaluating the prognosis of the head and neck carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…73 Nimotuzumab has a lower affinity, 74 and coincidently the adverse effects (mainly a skin rash) it provokes are much less serious compared with those of cetuximab. [75][76][77] Non-mutually exclusive hypotheses have been offered to explain its toxicity profile, including its preferential accumulation in tumor tissues, which have a higher antigen density; 75 the need of bivalent binding for exertion of its activity; 78 and its unique binding site on the EGFR extracellular domain III. 74 Nevertheless, in the case of 14F7 mAb-induced cell death, affinity plays a central role.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%